John Holmes Poetry - 'XXIX', 'XXX' and 'XXXI' - Holmes, John (Tufts Archival Research Center, 2019)
Page 7 of poetry notebook given to Muriel Simonson by John A. Holmes, circa 1930. Poems begin 'You said, This newest height of love', 'I have lingered over making them', and 'You say the love I give you'. Following page is blank.